Celebrity Endorsment, Kredibilitas, dan Niat Pembelian Kembali Pada First Media - Niki Sanjaya; Margaretha Pink Berlianto (Universitas Medan Area, 2022)
First Media as a broadband internet service provider optimizes marketing strategies through digital content using celebrity endorsements. The purpose of this study was to determine the effect of: (i) celebrity attractiveness on advertising credibility, brand credibility and brand satisfaction; (ii) celebrity trustworthiness on advertising credibility, brand credibility, and brand satisfaction; (iii) celebrity expertise on advertising credibility, brand credibility and brand satisfaction. This research method uses a quantitative approach by distributing questionnaires and involving 200 samples. Structural Equation Model (SEM) is used to determine the effect between constructs in this research model. The results of this study explain that in the case of First Media it is important to maintain the celebrity endorsement marketing strategy in increasing advertising credibility, brand credibility and brand satisfaction. Attractiveness and trust are one of the important factors of credibility. In this model it is known that advertising credibility, brand credibility, and brand satisfaction can be key factors for high repurchase intention.